ESBLs: A Clear and Present Danger? - Rishi H.-P. Dhillon; John Clark (Critical Care Research and Practice)
Extended spectrum β-lactamases (ESBLs) are enzymes produced by a variety of Gram negative bacteria which confer an increased resistance to commonly used antibiotics. They are a worrying global public health issue as infections caused by such enzyme-producing organisms are associated with a higher morbidity and mortality and greater fiscal burden. Coupled with increasing prevalence rates worldwide and an ever diminishing supply in the antibiotic armamentarium, these enzymes represent a clear and present danger to public health. This article aims to give an overview of the current situation regarding ESBLs, with a focus on the epidemiology and management of such infections.